ANALYSIS OF CASEMIX UNIT LABOR NEEDS USING THE ABK-KES METHOD AT MITRA SEHAT HOSPITAL - Ikawati, Fita Rusdian; Bulgis, Malikal; Mirda, Yudita Vera (Fakultas Ilmu Kesehatan, Universitas Ibn Khaldun, Bogor, 2025)
Mitra Sehat Hospital in Situbondo won the general conference title for the first time in 2018. However, the number of case mix officers in this hospital is only six, and they face many tasks as the workload is disproportionate to their number. This study used the ABK-Kes methodology to determine the staffing needs of the Casemix department of Mitra Sehat Situbondo Hospital in 2023. The methodology used was a descriptive study with a qualitative approach. The population of this study consisted of six Case Mix officials with different educational backgrounds, namely, four with D4 RMIK education, one with a D2 degree in informatics, and one with a high school diploma. Data were collected by observation and interviews. From the results of calculations using the workload analysis (ABK-Kes) methodology, the need for the Casemix section is 10 PMIK. Meanwhile, Mitra Sehat Hospital has only six PMIKs, indicating the need to add four more staff to reduce the high workload and optimize staff working hours.